Antioxidant And Antimicrobial Properties Of Tree Peony (Paeonia Suffruticosa) And Apple Flower (Malus Spp.) - Han, Ching Voon (2014)
In the present thesis, results revealed tree peony (Paeonia suffruticosa) and apple flower (Malus spp.) buds to have high crude protein (15.73 and 26.30%), fibre (13.11 and 16.51%), and carbohydrate (57.84 and 40.63%) contents. Both the flowers had significant amounts of essential amino acids and unsaturated fatty acids. Essential minerals present in tree peony and apple flowers were potassium (1540.37 and 1125.60 mg/lOOg), calcium (462.46 and 449.98 mg/100g), magnesium (241.51 and 164.23 mg/lOOg), sodium (12.75 and 20.06 mg/100g), and phosphorus (420.00 and 590.00 mg/lOOg), respectively. Heavy metals (cadmium, nickel, mercury, lead, and arsenic) were detected in trace amounts « 0.50 mg/lOOg) in both the flower buds. Besides, the total phenolic, total condensed tannin, total flavonoid, and total anthocyanin content of methanol, ethanol, and hot water extracts of tree peony ranged from 107.86 to 163.67 mg GAE/g sample, from 5.26 to 13.98 mg CE/g sample, from 22.18 to 30.06 mg CE/g sample, from 21.11 to 41.67 mg C-3-GEII00 g sample, respectively. While the total phenolic, condensed tannin, and total flavonoid content of apple flower ranged from 26.64 to 57.06 mg GAE/g sample, from 2.71 to 13.24 mg CE/g sample, from 31.63 to 78.12 mg CE/g sample, respectively. Anthocyanin was only detected in the methanol extract in 1.67 mg C-3- GEIIOO g sample. In term of antioxidant activities, the DPPH radical scavenging activity, FRAP and TAC of tree peony ranged from 82.27 to 92.10%, from 2.47 to 3.84 mmol Fe2+/g sample, and from 72.37 to 105.14 mg AAE/g sample, respectively.